Chlamydia trachomatis and Neisseria gonorrhoeae in HIV-infected Pregnant Women and Adverse Infant Outcomes. Issue 8 (August 2016) - Adachi, Kristina; Klausner, Jeffrey D.; Xu, Jiahong; Ank, Bonnie; Bristow, Claire C.; Morgado, Mariza G.; Watts, D. Heather; Weir, Fred; Persing, David; Mofenson, Lynne M.; Veloso, Valdilea G.; Pilotto, Jose Henrique; et al.
Abstract : Background: Sexually transmitted infections (STIs) in pregnancy such as Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) may lead to adverse infant outcomes. Methods: Individual urine specimens from HIV-infected pregnant women diagnosed with HIV during labor were collected at the time of infant birth and tested by polymerase chain reaction for CT and NG. Infant HIV infection was determined at 3 months with morbidity/mortality assessed through 6 months. Results: Of 1373 maternal urine samples, 277 (20.2%) were positive for CT and/or NG; 249 (18.1%) for CT, 63 (4.6%) for NG and 35 (2.5%) for both CT and NG. HIV infection was diagnosed in 117 (8.5%) infants. Highest rates of adverse outcomes (sepsis, pneumonia, congenital syphilis, septic arthritis, conjunctivitis, low birth weight, preterm delivery and death) were noted in infants of women with CT and NG (23/35, 65.7%) compared with NG (16/28, 57.1%), CT (84/214, 39.3%) and no STI (405/1096, 37%, P = 0.001). Death (11.4% vs. 3%, P = 0.02), low birth weight (42.9% vs. 16.9%, P = 0.001) and preterm delivery (28.6% vs. 10.2%, P = 0.008) were higher among infants of CT and NG-coinfected women. Infants who had any adverse outcome and were born to women with CT and/or NG were 3.5 times more likely to be HIV infected after controlling for maternal syphilis (odds ratio: 3.5, 95% confidence interval: 1.4–8.3). By adjusted multivariate logistic regression, infants born to mothers with any CT and/or NG were 1.35 times more likely to have an adverse outcome (odds ratio, 1.35; 95% confidence interval, 1.03–1.76). Conclusions: STIs in HIV-infected pregnant women are associated with adverse outcomes in HIV-exposed infected and uninfected infants.